Metal-insulator transitions in three-component Falicov-Kimball model within coherent potential approximation - Nguyen, Thi Huong; Le, Duc Anh; Hoang Anh, Tuan (Communications in Physics, 2022)
We apply the coherent potential approximation to study the three-component Falicov - Kimball model, in which single-component and two-component fermionic particles are mixed in an optical lattice. In the model, the heavy single-component fermionic particles are localized while the light two-component fermionic particles can hop in the lattice. At half-filling, two transitions from an insulator via a metallic state to a Mott insulator are found with increasing the particle correlations. By contrast, at third-filling, only one transition from the metallic state to the Mott insulating phase is observed for strong repulsive interactions. Our results are consistent with those obtained by the dynamical mean field theory as well as by the slave boson mean field approach.